IMAGE-GUIDED SURGERY IN THE SPINE: NEURONAVIGATION VS. FLUOROSCOPY - Guedes,Vinícius de Paula (2015)
Objectives:To evaluate the accuracy and the operative complications of implanting pedicle screws in the thoracic and lumbar spine, using computer-assisted surgery compared to the implantation technique using fluoroscopy.Methods:A retrospective study was conducted at the Hospital Universitário Cajuru PUC-PR from January 2000 to January 2009. Two groups of patients undergoing implant pedicle screws were analyzed (n=80). Group I received implant pedicle screws through fluoroscopy technique and group II, through neuronavigation technique. The accuracy of positioning of pedicle screws was evaluated using rating scales.Results:The accuracy was higher in group II, where 77.5% of the screws were correctly positioned, whereas there were only 28.5% in group I (p=0.001). There was a reduction of 95% (CI: 80-97%) in the risk of screws misplacement in group II. The average operation time was 312.2±78.1 minutes in group I and 270.3±41.4 in group II (p=0.004). Blood transfusion was needed in 28 patients in group I and 10 patients in group II (p=0.005), resulting in 64% risk reduction of blood transfusion in group II. Eight patients in group I underwent revision surgery whereas only one patient in the group II, that is, 75% of surgical revision risk reduction.Conclusion:The implantation technique of pedicle screws using neuronavigation is a more accurate method and has less operative complications compared with the technique that uses fluoroscopy.